Hybrid Docking-QSAR Studies of 1, 4-dihydropyridine-3, 5-Dicarboxamides as Potential Antitubercular Agents - Rasouli, Yasaman; Davood, Asghar (Current Computer - Aided Drug Design, 2018)
Background: Tuberculosis is one of the main medical problems and some people are suffering still from this infectious disease. 1, 4-dihydropyridines are multi-target ligands that recently are recognized as anti-tubercular agents. Methods: In the current research, computational studies were conducted of some synthesized 1, 4- dihydropyridine-3, 5-dicarboxamides in non-hydrolyzed and hydrolyzed forms to find the drugreceptor interactions profile. Results: Among equations obtained for non-hydrolyzed compounds, the model with better statistical parameters such as R2= 0.9462, q2 of LOO= 0.8318 and q2 of LMO= 0.7987 was considered as the best one and EEig08d, LAI, Mor23m, GATS3e, Mor28m descriptors were identified as the most significant factors that affect the biological activity of non-hydrolyzed compounds. Conclusion: In the hydrolyzed compounds, the model which has R2= 0.9731, q2 of LOO= 0.91154462 and q2 of LMO= 0.742 was considered as the best one and Mor27e and BEHv2 were also revealed as the most important descriptors in hydrolyzed compounds.
Keywords: Docking